Elastic intramedullary nailing combined with methylprednisolone acetate injection for treatment of unicameral bone cysts in children: a retrospective study. (2021) - Zhou, JianWu; Ning, ShangKun; Su, Yuxi; Liu, Chuankang
Abstract: Purpose: The aetiology of unicameral bone cysts (UBCs) is unclear. This study aims to evaluate the feasibility of elastic intramedullary nailing (EIN) combined with injections of methylprednisolone acetate (MPA) for the treatment of UBCs in children. Methods: We retrospectively analyzed 53 children with UBCs in our hospital between January 2010 and April 2016. A total of 24 patients (Group A) were treated by EIN and MPA, whilst 29 patients (Group B) were treated by curettage, bone grafts and EIN fixation. The radiographs of the UBCs were evaluated following the Capanna criteria. All patients were followed-up on the third, sixth, 12th, 24th and 36th months. Fixation time, hospitalization time and complications were evaluated. Results: In Group A, the mean number of MPA injections was 1.8 (1 to 3). Based on radiographic evaluation, eight patients were healed (Capanna grade I), 14 were healed with residual cysts (Capanna grade II), one showed recurrence (Capanna grade III) and one showed no response to the treatment (Capanna grade IV). In Group B, 11 patients were evaluated as Capanna grade I, 12 as Capanna grade II, three as Capanna grade III and three as Capanna grade IV. There was significant difference in the early postoperative function activity (p < 0.001), hospitalization time (p = 0.028), blood loss during surgery (p < 0.001) and surgery time (p < 0.001). Conclusion: The combination of EIN and MPA for the treatment of UBCs in children is feasible, has little operative trauma, short surgery time, short hospitalization time, less blood loss and a low risk of incision infection. Level of evidence: III